Organizational Reactions of Russian NGOs to 2012 Legislative Changes - Andrei Semenov; Vsevolod Bederson (Journal of Economic Sociology, 2017)
In this article, we examine organizational reactions in the Russian third sector to adoption of the so-called “Foreign Agents” law in July 2012. Within the framework of organizational and resource dependence theories, we analyze state “licensing” policy in relation to civil society organizations and the tightening of regulation in the sector. We propose a typology of NGOs based on resource flows and rules of access, enabling a comparison of the organizational reactions of Russian NGOs to the new regulations. The study is grounded empirically in interviews with 19 representatives of NGOs in nine regions, along with data from internal documents, official statistics, and media reports. Our main argument is informed by the open systems theory of organizations, positing that growing state intervention in the third sector increasingly impacts NGOs’ organizational features, regardless of type. The imposition of a listing of organizations “with foreign agent functions” has affected relations between the state, business, and the third sector, limiting access to resources for the latter. Measures like presidential grants and subsidies to compensate for resource shortfalls tend to be conditional, for example, on political loyalty. More generally, these environmental changes have hindered the capacity of third sector organizations to sustain professionalization. However, Russian NGOs have demonstrated considerable resilience in adapting to these changes through diffusion of organizational forms to minimize the costs of new legislation.